|3y| = 15 : 2,5
|3y| = 6
|y| = 6 : 3
|y| = 2
y1 = 2; y2 = -2
Ответ:
Пошаговое объяснение:
7,4x-12,3x-1,56+2,3x=2,6x
x(7,4-12,3+2,3-2,6)=1,56
-5,2x=1,56
x= 1,56:(-5,2)
x= -0,3
нижнее уравнение умножаем на 3
из верхнего вычитаем нижнее, остаётся
-x=-20
умножаем на -1
x=20
вставляем в нижнее
3 * 20 + y = 9
60 + y = 9
y = 9 - 60
y = -51
Ответ: -5/6
Пошаговое объяснение:
7/18 *(-1 4/7) - (-4/21)*( -1 1/6)
1)7/18 *(-1 4/7)= 7/18 *(-11/7) = -11/18
2)(-4/21)*( -1 1/6)= (-4/21)*( -7/6)=2/9
3)-11/18 - 2/9= -11/18 - 4/18 = -15/18 =-5/6